The Big Dipper - Branley, Franklyn Mansfrey50; Coxe, Molly (New York : HarperCollins, 1991)
Explains basic facts about the Big Dipper, including which stars make up the constellation, how its position changes in the sky, and how it points to the North Star.
Keywords: Constellations; Stars; Ursa Major -- Juvenile literature; Ursa Major